'Academic freedom' in Indian higher education setting / Satya Sundar Sethy - Sethy, Satya Sundar (Universiti Teknologi MARA, 2021)
In the Indian higher education (HE) setting, what 'academic freedom' of students and faculty members constitutes has not been discussed in detail. As a result, many faculty members and students have discerned 'academic freedom' as freedom from external control and influence. It is noticed that faculty members and students are often misinterpreting and misconstruing the concept of 'academic freedom' as 'legal freedom' and confused it with 'civil and political rights'. This creates a hurdle to achieve the aims and objectives of Indian HE institutions. Against this backdrop, the paper discusses the concept of 'academic freedom' and its importance in the higher education setting. It examines the relationship between 'academic freedom' and 'university autonomy' in the Indian context. It discusses the HE institution's social responsibilities concerning the notion of 'academic freedom'. It delineates faculty member's and student's academic freedom in the Indian higher education setting. It submits that 'academic freedom' is not to be treated as 'legal freedom'. But it is an essential requisite for quality teaching-learning activities, productive and rewarding research works in higher education. The paper adopts a qualitative methodology that subsumes descriptive, evaluative, and interpretative approaches to derive its conclusion.